2010
DOI: 10.1021/jp101683z
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption, Solvation, and Deliquescence of Potassium Bromide Thin Films on SiO2 Studied by Ambient-Pressure X-ray Photoelectron Spectroscopy

Abstract: The adsorption of water on KBr thin films evaporated onto SiO 2 was investigated as a function of relative humidity (RH) by ambient pressure X-ray photoelectron spectroscopy. At 30% RH, adsorbed water reaches a coverage of approximately 1 ML (monolayer). As the humidity continues to increase, the coverage of water remains constant or increases very slowly until 60% RH, followed by a rapid increase. At low RHs, the Br/K ratio on a submonolayer-thick film drops to less than 0.1, as a result of loss of Br atoms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 64 publications
1
37
3
Order By: Relevance
“…Details of this estimation are described elsewhere. 17,27 We found that the estimation of a peak area has a deviation of 5%. This leads to an error of about 610% in the calculated water layer thicknesses.…”
Section: B Ap-xps Experimentsmentioning
confidence: 90%
“…Details of this estimation are described elsewhere. 17,27 We found that the estimation of a peak area has a deviation of 5%. This leads to an error of about 610% in the calculated water layer thicknesses.…”
Section: B Ap-xps Experimentsmentioning
confidence: 90%
“…OH À anions are also expected to be less prone to beam damage than, for example, halides 37 , due to the presence of water vapour. The CsOH/NaOH layer was prepared by depositing a droplet of 0.01 M CsOH/0.01 M NaOH solution onto the sample.…”
Section: Methodsmentioning
confidence: 99%
“…where h is Planck's constant, E 1/2 is the full-width at half maximum of the absorption peak and v F is the Fermi velocity of the electrons. We believe the cesium nano-rods and free cesium on the grain surfaces are eroded by the reaction 2Cs + 2H 2 O = 2CsOH + H 2 (5) Arima et al [32] have observed that this reaction precedes slowly for atmospheric relative humidity (RH) less than 30% and increases with RH. Also, there is a near exponential increase in the rate of reaction for RH above 80%.…”
Section: Aging and Effect Of Ambient Atmospherementioning
confidence: 99%